HISTORICAL CHANGES IN THE AREA UNDER FOREST—ESTIMATION APPROACH BASED ON CARTOGRAPHIC RESOURCES - Aleksandar Popović; Biljana Šljukić; Dragan Borota (Zbornik Radova: Geografski institut "Jovan Cvijić")
This paper analyzes changes in forested areas, as depicted in topographic maps, within the historical context of their publication in Serbia. The research focuses on the experimental field “Goč-Gvozdac” of the University of Belgrade – Faculty of Forestry, with additional reference to changes in Central Serbia. Changes were assessed across historical periods using four reference topographic maps: from 1893, 1929, 1971, and 1985. Data on shifts in forested areas (categorized as forest and other land) were obtained by vectorizing scanned analog maps using manual GIS editing tools. Additionally, currently available spatial data sets of land cover/use for 2021 were utilized for the analysis. The forest distribution across different geological formations was also evaluated. The results indicate a continuous increase in forested areas within the experimental field, rising from 77.6% in 1893 to 89.3% in 1985, and reaching 95.1% by 2021. The most significant increase occurred during the first reference period (1983–1929), while the smallest growth was observed in the last one. Data for Central Serbia also reveal a general upward trend in forested areas throughout the 20th century, consistent with findings from the experimental field. However, analyses in the 21st century indicate only minor changes in the forested area. The historical data on forest area changes provide valuable insights, enhancing our understanding of forest development and informing better forest management planning, organization, and activity implementation. This is significant for enhancing knowledge from educational and scientific research perspectives, as well as providing the foundation for forest management in preservation and qualitative improvement.